Molecular Docking: Analysis of Mahogany Plant Compounds (Swietenia macrophylla King) against the ACE2 Enzyme of SARS-CoV-2 - Amrulloh, Lalu Sanik Wahyu Fadil; Khairani, Ayudia Cipta (Journal of Islamic Pharmacy, 2025)
Various treatment approaches have been attempted to tackle severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)  infection. One approach to develop new drugs is through the utilization of medicinal plants. Mahogany (Swietenia macrophylla King) is one of the plants that is thought to have potential as an inhibitor of SARS-CoV-2. This study aims to determine the anti-SARS-CoV-2 potential of compounds in mahogany plants that have good interactions and interaction patterns with angiotensin-converting enzime 2 (ACE2) receptors. A total of ten mahogany plant compounds were tested for drug-likeness based on Lipinski screening which will then be docked to the ACE2 molecular target, using the molecular docking method. The parameters observed were binding energy values and amino acid residues. The results of molecular docking showed that the compounds predicted to have the highest binding affinity and have similar interaction patterns with natural ligands to the ACE2 molecular target were secomahoganin and stigmasterol. The secomahoganin and stigmasterol compounds are predicted to have good interactions with the ACE2 receptor.